20. Acute and sub-chronic oral toxicity studies of “Tri 02” powder in experimental animals - Thai, Nguyen Thi; Anh , Pham Thi Van; Ha, Nguyen Thị Thu; Quyen, Do Linh; Phuc, Nguyen Van; Hien, Dang Thi Thu (Tạp chí Nghiên cứu Y học, 2023)
This study aims to assess the acute and sub-chronic oral toxicity of “Tri 02” powder in experimental animals. According to World Health Organization Guidance, acute toxicity study was conducted using Swiss mice. LD50 was determined by Litchfield-Wilcoxon method, and sub-chronic toxicity of “Tri 02” at two doses (2.4 g/kg b.w/day and 7.2 g/kg b.w/day) was assessed in Wistar rats for four uninterrupted weeks. Abnormal behavior, toxic symptoms, and death were observed for 7 consecutive days to assess the effects of acute toxicity. The general behavior of the rats was observed daily, and their body weight was recorded weekly. Hematological analysis and biochemical analysis were conducted before treatment, and at 2 and 4 weeks of treatment. Macroscopic examination and histopathological examination of several organs were conducted at the end of the treatment period. The results suggested that “Tri 02” at the highest dose used for mice (187.5 g/kg b.w) did not show acute toxicity and the LD50 was determined. In terms of the sub-chonic toxicity test, after oral administration of “Tri 02” powder, hematological parameters, hepato-renal functions and microscopic images of liver and kidney at both doses were similar to the control group. In conclusion, “Tri 02” powder did not produce the acute and subchronic oral toxicity in experimental animals.